2018
DOI: 10.4049/jimmunol.1800553
|View full text |Cite
|
Sign up to set email alerts
|

Unique Composition of Intronless and Intron-Containing Type I IFNs in the Tibetan Frog Nanorana parkeri Provides New Evidence To Support Independent Retroposition Hypothesis for Type I IFN Genes in Amphibians

Abstract: full#ref-list-1 , 25 of which you can access for free at: cites 69 articles This article average * 4 weeks from acceptance to publication Fast Publication! • Every submission reviewed by practicing scientists No Triage! • from submission to initial decision Rapid Reviews! 30 days* • Submit online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 69 publications
6
68
0
Order By: Relevance
“…There was a total of 437 positions in the final dataset. In contrast to the previously known several fish-like intron-containing amphibian IFNs, recent studies revealed that amphibians are unique to have both fish-like intron-containing and amniotic intronless IFNs, which molecularly and immunologically stamp their amphibiotic position in vertebrate evolution [12,13,16]. Legends and Abbreviations: IFN-I, type I IFNs (including amniotic intronless IFNA, IFNB, IFNE, IFNK, IFNW, respectively, for the genes of IFN-α, -β, -ε, -κ, -ω; and diverse amphibian intron-containing, XaIFN For instance, extensive analysis of current genome assemblies of Xenopus tropicalis and Xenopus laevis at NCBI (https://www.ncbi.nlm.nih.gov/genome/?term=Xenopus) and Xenobase (http://www.…”
Section: Ifn-mentioning
confidence: 95%
See 4 more Smart Citations
“…There was a total of 437 positions in the final dataset. In contrast to the previously known several fish-like intron-containing amphibian IFNs, recent studies revealed that amphibians are unique to have both fish-like intron-containing and amniotic intronless IFNs, which molecularly and immunologically stamp their amphibiotic position in vertebrate evolution [12,13,16]. Legends and Abbreviations: IFN-I, type I IFNs (including amniotic intronless IFNA, IFNB, IFNE, IFNK, IFNW, respectively, for the genes of IFN-α, -β, -ε, -κ, -ω; and diverse amphibian intron-containing, XaIFN For instance, extensive analysis of current genome assemblies of Xenopus tropicalis and Xenopus laevis at NCBI (https://www.ncbi.nlm.nih.gov/genome/?term=Xenopus) and Xenobase (http://www.…”
Section: Ifn-mentioning
confidence: 95%
“…We therefore updated the current repertoire of IFN gene loci in X. tropicalis: The co-existence of 14 Figure 1) [13]. A new study in a Tibet frog species (Nanorana parkeri) reinforced the co-existence of both intron-containing and intronless IFN genes in amphibians [16]. However, the expansion of antiviral IFN genes in different amphibian species, especially the intronless ones, seems species-independent.…”
Section: Ifn-mentioning
confidence: 96%
See 3 more Smart Citations